Attitudes and motivation of Malaysian secondary students towards learning English as a second language: a case study - Thang, Siew Ming; Ting, Siew Ling; Nurjanah Mohd Jaafar (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
The English Language has always played a significant role in Malaysia’s quest of becoming a developed nation. Despite this, the English proficiency level of Malaysian students is far from satisfactory. What are the reasons for this? Motivational studies have shown that Malaysian students realise the importance of English for their future development and that students are extrinsically motivated by factors such as the desire to get good grades, opportunities to further their studies and career advancement to improve their English. However, in these cases extrinsic motivation does not necessarily translate to better performance in English. Most of these studies were undertaken in tertiary settings. Thus, there is a possibility that secondary school students may not be aware of the importance of English for their future. Conversely, it is also probable that these problems stem from a lack of motivation and poor attitude beginning from secondary school. This paper discusses the findings of a study undertaken to investigate these issues further by carrying out a questionnaire survey on attitudes and motivation of a group of secondary school students in East Malaysia towards learning English as a Second Language. The study reveals an overall positive attitude towards learning English by Art and Science students. Further Science students and higher proficiency students show more interest in improving their English. In addition, the findings reveal a positive relationship between higher proficiency level and positive attitudes and motivation to learn English.